Static and dynamic material properties of CFRP/epoxy laminates - Zhang, Xihong; Hao, H.; Shi, Y.; Cui, J.; Zhang, X. (Elsevier BV, 2016)
Carbon fiber reinforced polymer (CFRP) has been extensively used to strengthen structures owing to its outstanding mechanical properties. With an increasing threat from terrorist bombing attacks and accidental explosions, the application of CFRP has been extended to mitigate the effect of blast loading on structures. A better understanding of the dynamic material properties of CFRP/epoxy laminates at high strain rates is therefore needed for more reliable analysis and design of CFRP strengthened structures under dynamic loadings. In this study, the unidirectional tensile properties of CFRP (SikaWrap®-230C) and epoxy resin (Sikadur®-330) laminates is investigated experimentally over a wide range of strain rates. Quasi-static and low-speed tensile tests are conducted at strain rates varying from 7 × 10−5 s−1 to 0.07 s−1. Then, high-speed tensile tests are performed using a high-speed servo-hydraulic testing machine at strain rate from about 10 s−1 to 240 s−1. The testing results show that both the tensile strength and the stiffness of the CFRP/epoxy laminates are insensitive to loading speed when the strain rate is less than 50 s−1. However, when strain rate is over 50 s−1, both the tensile strength and the coupon stiffness increase with the increase of strain rate. High-speed camera images are used to assist inspecting the failure modes of CFRP/epoxy laminates. It is found that under high-strain rate tension CFRP/epoxy laminates fail differently from that at low-strain rate. The different failure mode is believed to contribute to the increment of laminate strength. The testing data are analyzed together with available testing results on CFRP/epoxy laminates at various strain rates. Empirical formulas of dynamic increase factor for CFRP material are derived for better prediction of material strength at various strain rates.